Coverage performance analysis of genetic algorithm controlled smart antenna system - Badjian M.M.; Thirappa K.; Kiong T.S.; Paw J.K.S.; Krishnan P.S. (2023)
In this paper, an innovative type of smart antenna based on genetic algorithm (GA) has been developed and tested. The new GA embedded solution simplifies the control of smart antenna system with increment of the accuracy of beam coverage and decrement of beam availability in compare with the conventional switch beam smart antenna. Scanning antenna of the system determined the location of mobile users through its band passed radio frequency power detector circuitry. GA then operates to optimize and steer the coverage beams to cater for dynamic users' distribution with minimum power usage. The experiment with GA embedded control system smart antenna shows good result in beam formation and steering to handle mobile users. 2010 IEEE.